Budgeting in Thailand - Blazey, Andrew (OECD Publishing, 2021)
This review provides an overview of the budgetary landscape in Thailand and identifies the legal and constitutional aspects that impact on the planning, preparation and reporting of the budget. It then discusses strategic planning elements of the budget, specifically fiscal objectives, medium-term planning, capital investment, the management of fiscal risk in budgets and performance budgeting. It focuses on the development and preparation of the budget, the oversight of the execution of the budget, and the accounting and reporting functions supporting the budget. The final section considers the oversight and accountability of the budget from the perspective that is external to the preparation and decision making of the government. It looks at the role of parliament and independent institutions as well as the transparency, openness and accessibility of the budget. The analysis undertaken in this review is based on the OECD Recommendation of the Council on Budgetary Governance